Tracking Regret and Guilt: The Context of Harm and Trait Mindfulness - Cleoputri Yusainy; Muhammad Haikal Azaim Barlaman; Jeremy Alexander Timothy; Salsabila Salsabila; Wahyu Wicaksono (Gadjah Mada Journal of Psychology (GamaJoP), 2023)
Being exceedingly social creatures, each and every decision that an individual human makes carries with it consequences and risks that may endanger not only themselves (intrapersonal harm), but also others (interpersonal harm). This experiment (N = 215 undergraduates; 63.36% female; Mage = 21.86, SD = 2.56) compared the impact of contextual harm on emotions of regret and guilt, and examined whether the role of a trait-relevant predictor in the form of mindfulness on regret/guilt could be explained by tendency of being under-engaged (trait alexithymia) and over-engaged (trait rumination) of affective experiences. In line with our predictions, (i) interpersonal harm aroused more guilt than intrapersonal harm, but the levels of regret between the two contexts were not unalike; (ii) mindfulness negatively correlated with alexithymia, rumination, regret, and guilt; and (iii) after controlling for type of harm, the relation between mindfulness and regret/guilt was mediated by alexithymia and rumination. Although guilt depends heavily on interpersonal context while regret is induced more globally, mindfulness inversely predicts the levels of both emotions through alexithymia and rumination